RANCANG BANGUN SISTEM PENGENDALI SUHU BARREL PADA MESIN SINGLE SCREW EXTRUDER MENGGUNAKAN METODE PID BERBASIS ESP32 - Yani Prabowo; Anwar Rifai; Jan Everhard (SKANIKA: Sistem Komputer dan Teknik Informatika, 2026)
Barrel temperature stability is a crucial factor in the polymer extrusion process, as temperature fluctuations directly affect melt viscosity and final product quality. This study designed a temperature control system for a single-screw extruder using an ESP32 microcontroller to compare the performance of the Proportional-Integral-Derivative (PID) method against a system without control (open loop). The research methodology involved testing various screw rotation speeds from 50 to 200 RPM to observe barrel temperature stability and melt homogeneity. The determination of the PID parameters in this study was based on the evaluation of the open-loop system's thermal response mapping, yielding optimal tuning values of Kp = 4.8, Ki = 0.09, and Kd = 55. The test results showed that the system without control experienced temperature fluctuations of ±8–12°C, while the PID controller successfully maintained temperature stability with a low deviation of ±1–3°C. Furthermore, the PID system was able to automatically compensate for temperature increases caused by material friction at high speeds. The implementation of PID control was proven to increase thermal stability by up to 80% compared to conventional systems. These results demonstrate that the use of PID algorithms on microcontrollers ensures a more precise and stable plastic extrusion process compared to traditional methods.